A task-based approach to developing context-specific agility - Jeffreys, I. (Strength and Conditioning Journal, 2011)
Effective movement is a key element of elite sports performance in a range of sports, and agility training has become an important element in many sports performance enhancement programs. Traditionally, agility training has focused on the execution of closed drills that allow for the development of effective movement patters but may not optimally transfer directly to enhanced sports performance. This article aims to examine the nature of reactive agility and provide a theoretical support for the application of reactive agility exercises and also suggests methods of delivering these exercises to maximize the transfer to enhanced sports performance.